Physical Function Impairment of Older, HIV-Infected Adults Is Associated with Cytomegalovirus Immunoglobulin Response - Erlandson, Kristine M. (AIDS Res Hum Retroviruses, 2015)
Cytomegalovirus (CMV) is associated with poor outcomes, including physical function impairment, in older HIV-uninfected adults. Whether CMV is associated with physical functional impairment in HIV-infected adults is unknown. The primary objective of this study was to determine the relationship between CMV-specific humoral and cell-mediated immune responses with functional impairment in well-controlled HIV infection. In a case-control study, low-function cases were matched by age, gender, and time from HIV diagnosis to high-function controls. Quantitative CMV IgG and %CMV-specific CD8(+) and CD4(+) T cells (interferon-γ expression following CMV pp65 stimulation) were used to estimate physical function. Among 30 low-function cases and 48 high-function matched controls, CMV IgG ranged from <10 to 8,830 EU/ml, including four controls with results <10 EU/ml. Each log(10) increase in CMV IgG was associated with 5-fold greater odds of low function (p=0.01); these findings were robust to adjustment for concomitant CD4(+) count, tobacco use, and age; to exclusion of subjects with CMV IgG <10 EU/ml; and to adjustment for hepatitis C viremia. %CMV-specific CD4(+) or CD8(+) T cells were not associated with low function. In bivariable models, the relationship between CMV IgG and physical function was attenuated and was no longer significant when including IL-6, CD4/CD8 ratio, or the Veterans Aging Cohort Study Index score. High levels of CMV-specific IgG were associated with impaired physical function. Attenuation of the strength of this association in bivariable models suggests an indirect relationship mediated by systemic inflammation and immune suppression.